2012
DOI: 10.1002/acr.21707
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric properties of observer‐assessed impairment tests used to evaluate hip and groin impairments: A systematic review

Abstract: Objective. To recommend the most suitable observer-assessed impairment tests in people with hip and/or groin pathologies by conducting a systematic review of the clinimetric properties of these tests. Methods. Electronic searches were performed in the Cochrane, PubMed, CINAHL, Embase, SPORTDiscus, and PsycINFO databases up to August 2011. Two reviewers independently rated the measurement properties of clinical tests of impairments, defined by the International Classification of Functioning, Disability and Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…However, evidence is lacking with regard to inter-rater reliability for methods of hip strength measurement, and responsiveness of testing methods to measure change (online supplementary appendix). 19 20 Therefore, we recommend that clinicians use objective methods to measure muscle strength in the assessment and management of hip-related pain. However, the interpretation of these results should consider potential intratester and intertester differences, and instrument measurement error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence is lacking with regard to inter-rater reliability for methods of hip strength measurement, and responsiveness of testing methods to measure change (online supplementary appendix). 19 20 Therefore, we recommend that clinicians use objective methods to measure muscle strength in the assessment and management of hip-related pain. However, the interpretation of these results should consider potential intratester and intertester differences, and instrument measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore recommended that these tasks be included in the clinical assessment of this patient population. There is limited evidence that the intratester and intertester reliability is acceptable for the SEBT and single-leg standing test,20 23 while acceptable intertester reproducibility in the clinic has not been established for the assessment of single-leg squat and step-down tests (box 1, online supplementary appendix).…”
Section: Discussionmentioning
confidence: 99%
“…For now, studies rely on comparisons. Inter-rater reliability of ROM measurements can vary as described in a recent review of measures used to assess hip osteoarthritis by Dobson et al [7] For this reason, the authors of this study (HP and DH) assessed inter-rater reliability and used the most reliable measure for this study [30]. Studies specifically comparing genders have reported women to have greater active hip internal rotation, external rotation [33], passive hip flexion [34], and internal rotation as compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we included patient- and self-reported measures as well as observer based measures on physician-patient communication. Nevertheless, prior studies applied the COSMIN criteria to a range of measures [19] , [20] . For the instruments that use observer codings or ratings, the items of the COSMIN checklist are not always applicable (e.g.…”
Section: Methodsmentioning
confidence: 99%